Centrifugation based separation of lithium iron phosphate (LFP) and carbon black for lithium-ion battery recycling - Wolf, Andreas; Flegler, Andreas; Prieschl, Johannes; Stuebinger, Thomas; Witt, Wolfgang; Seiser, Felix; Vinnay, Thomas; Sinn, Tabea; Gleiß, Marco; Nirschl, Herrmann; Mandel, Karl (Chemical Engineering and Processing, 2021)
Semi-continuous centrifugation is suggested as promising method to separate battery active materials from aqueous multi-component agglomerate dispersions. This is of special interest for direct recycling of active materials from decommissioned lithium-ion batteries. The separation of lithium iron phosphate (LFP) from carbon black C65 could be achieved with separation efficiencies of 90–100 % for LFP and 40–90 % for C65. The working parameters of the centrifuge, namely volumetric flow rate and rotational speed, were varied within a design of experiments study to find an optimum at 65 mL min−1 and 20,000 rpm, where at least 97 % of the LFP is separated in the centrifuge, while as much C65 as possible is pushed into the centrate. Furthermore, the separation mechanism was discussed by analyzing particle size distributions and the sediment build-up. High rotational speeds and low volumetric flow rates lead to significant radial and axial gradients in terms of carbon content in the sediment. LFP that was extracted from the sediment after centrifugation at the optimum conditions exhibited 98 % of the initial specific capacity.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Battery recycling; Centrifuge; Design of experiments; Lithium iron phosphate; Particle separation; Particle size analysis